Case in Russian : a sign-oriented approach - Beytenbrat, Alexandra (Studies in functional and structural linguistics, 2015)
This volume presents an analysis of Russian case from a sign-oriented perspective. The study was inspired by William Diver's analysis of Latin case and follows the spirit of the Columbia School of linguistics. The fundamental premise that underlies this volume is that language is a communicative tool shaped by human behavior. In this study, case is viewed as a semantic entity. Each case is assigned an invariant meaning within a larger semantic system, which is validated through numerous examples from spoken language and literary texts to illustrate that the distribution of cases is semantically.